Preparation method of degradable super absorbent resin

Through the aqueous solution polymerization process, carbon nanomaterials and starch were introduced to prepare a degradable and absorbable water resin that was resistant to temperature, salt and compressive, which solved the shortcomings of existing resins in temperature, salt and compressive properties, and achieved the degradability of the resin.

CN119613616AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311180156.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-14
Estimated Expiration
2043-09-13

AI Technical Summary

Technical Problem

The existing highly absorbent resins have shortcomings in temperature, salt and compressive properties, and are difficult to achieve degradability.

Method used

By adopting the aqueous solution polymerization process, by introducing carbon nanomaterials and starch and adjusting the process conditions, a degradable and absorbable water resin that is temperature-resistant, salt-resistant and compressive-resistant is prepared.

Benefits of technology

The obtained resin not only has high water absorption, but also has good temperature, salt and compressive properties, and is also degradable, suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of polymer synthesis and application, and particularly relates to a preparation method of degradable super absorbent resin. The starch and the carbon nanomaterial nitrile titanium are introduced into a polymerization system, all process conditions are adjusted, the degradable water-absorbent resin resistant to temperature, salt and pressure is obtained, and the defects that although the water absorption rate of common polyacrylamide series water-absorbent resin is high, the temperature resistance and salt resistance are poor, the gel strength after water absorption is low, and the common polyacrylamide series water-absorbent resin is not degradable and not resistant to pressure are overcome. The prepared resin belongs to degradable environment-friendly resin and can be applied to the aspects of oil extraction, water injection and leakage stoppage of an oil field, environment-friendly sewage treatment, agriculture and forestry water and soil conservation, agricultural water storage, sanitary materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer synthesis and application, and specifically relates to a method for preparing a degradable high water-absorbent resin. Background Art

[0002] Super absorbent resin (SAP for short) is a hydrophilic polymer compound with a network structure and a low degree of cross-linking. It is insoluble in water and organic solvents, but can absorb up to 100 or even 1,000 times its own weight in water. It absorbs water very quickly, is not easy to lose water, and has a strong water retention capacity.

[0003] Since the establishment of Flory's theory in the 1950s and 1960s, super absorbent resin has developed into a discipline with multiple types, multiple uses, huge output and in-depth theoretical research at home and abroad. Its products mainly include: non-ionic, anionic, cationic, zwitterionic and five series of hydrophilic groups, including sulfonic acid type, carboxylic acid type, phosphoric acid type, tertiary amine, quaternary ammonium, amide, ether, starch and their combination types. The highest water absorption rate product can reach 5000g / g water absorption multiples. It is widely used in agriculture, forestry, horticulture, medicine, physiological and sanitary products, construction, fire protection materials, daily chemicals, papermaking, oilfield chemicals and many other industries. The raw materials used in the above five series of absorbent resins are mainly acrylic acid, acrylamide, acrylonitrile, sodium acrylate, sulfonate, tertiary amine salt, quaternary ammonium salt, starch, etc. Different application fields have different requirements for absorbent resins. In the fields of sanitation, agriculture, forestry, water and soil moisture retention, gardening, etc., attention is paid to indicators such as high water absorption rate, fast water absorption rate, and degradability. In terms of engineering plugging, high compressive strength and strong toughness are required to prevent breakage and failure during use. In oil field production, oil adjustment, oil flooding plugging, especially in the high-temperature and high-salt oil reservoir environment of "three productions", attention is paid to the temperature and salt resistance of the water-absorbing gel. In the water-absorbing resin obtained by multi-polymerization, because it carries carboxylate, sulfonate, phosphate, tertiary amine, quaternary ammonium, starch and other groups, the water-absorbing resin has the advantages of temperature resistance, pressure resistance, high water absorption rate, and fast water absorption rate. Although the acrylamide-based water-absorbing resin has a high water absorption rate, its temperature and pressure resistance is relatively low, which affects its use. Song Xuefeng's "Water Absorption and Anti-fragmentation Properties of Modified Polyacrylamide Absorbent Resin" discusses that the high degree of fragmentation of the resin is caused by the high water absorption rate. Therefore, water absorption rate and gel strength are two factors that must be considered. Simply pursuing high water absorption rate is not advisable. The article also studies various methods to improve the compressive strength of the gel, mainly the grafting modification method, but this method is cumbersome and the effect is average.

[0004] In particular, further improvement is urgently needed in terms of heat resistance, salt resistance and degradability. In "Synthesis and Water Absorption Performance of P (AA / AMPS) Salt-Resistant Super Absorbent Resin", Song Tianwen used the reverse suspension method to prepare a water-absorbent resin with good salt resistance. However, the water-absorbent resin synthesized with acrylic acid, a by-product of petroleum processing, is non-renewable, and the product is not easy to degrade and has poor environmental compatibility. The use of natural green materials to prepare super absorbent materials is one of the current hot topics. In "Preparation and Characterization of AA / AMPS-Starch-OMMT-Composite Salt-Resistant Water-Absorbent Resin", Li Kun prepared a resin with high salt water absorption by adding montmorillonite and AA, AMPS and starch graft copolymerization. The article emphasized that the gel strength of the resin after water absorption was improved by adding starch and montmorillonite, but did not explain whether it is degradable. In "Synthesis Research of Starch Grafted Polyacrylamide Water-Absorbent Resin", Zhang Teng focused on the process conditions for resin synthesis, and did not conduct in-depth research on the degradation of the resin. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a degradable super absorbent resin. The process is simple, and the prepared resin is degradable, has high water absorption, and has good heat resistance, salt resistance, and pressure resistance.

[0006] The present invention is achieved through the following technical solutions: The method for preparing the degradable super absorbent resin of the present invention comprises the following steps: (1) Dispersion of carbon nanomaterials: Mix the carbon nanomaterials and deionized water and disperse them by ultrasonic until there are no flocs; (2) Starch gelatinization: Add starch to the solution obtained in step (1), stir evenly, and heat to gelatinize to obtain a carbon nanomaterial starch solution; (3) Aqueous solution polymerization: acrylamide (AM), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), a hydrolyzing agent, a cross-linking agent and the carbon nanomaterial starch solution obtained in step (2) are added into a closed polymerization vessel. After the polymerization vessel is deoxygenated, an initiator dissolved in deionized water is added into the polymerization vessel to carry out a polymerization reaction to obtain a polymerized colloid product. (4) Colloid post-treatment: granulating, drying and crushing the polymerized colloid product to obtain the final product, i.e., the degradable super absorbent resin.

[0007] Preferably, the carbon nanomaterial is titanium nitrile (TiCN), and the size of the nanoparticles is 20-40 nanometers.

[0008] In step (1), the ultrasonic frequency is 25000-30000 Hz, and the ultrasonic time is 25-35 minutes.

[0009] In step (2), the gelatinization temperature is 65-75°C and the gelatinization time is 25-35 minutes.

[0010] In step (3), the polymerization reactor is deoxygenated by passing nitrogen gas to make the oxygen content of the polymerization system less than 0.2 ppm; At the beginning of the polymerization reaction, the polymerization reactor temperature is 10~40°C, and as the polymerization reaction proceeds, the material temperature reaches 90~100°C. The reaction time is 4~6 hours.

[0011] In the preparation process of the degradable super absorbent resin, the required raw material amounts are as follows by weight: 0.0003 parts of carbon nanomaterials, 73.6 parts of deionized water, 2 parts of starch, 15 parts of acrylamide, 5 parts of 2-acrylamido-2-methylpropanesulfonic acid, 4.4 parts of hydrolyzing agent, 0.03 parts of crosslinking agent, and 0.048 parts of initiator.

[0012] The amount of deionized water used in step (1) is 70 parts, and the amount of deionized water used in step (3) is 3.6 parts.

[0013] The hydrolyzing agent is sodium hydroxide, sodium carbonate or sodium bicarbonate, preferably sodium bicarbonate.

[0014] The crosslinking agent was N,N-methylenebisacrylamide (MBA).

[0015] The initiator is a combination of an oxidant and a reductant in a mass ratio of 1:1, the oxidant is one or more of ammonium persulfate, potassium persulfate or sodium persulfate, and the reductant is one or both of sodium bisulfite and sodium sulfite.

[0016] In step (4), the drying temperature is 60-90°C and the solid content is 96%.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adopts an aqueous solution polymerization process, has a stable reaction and a simple process. By introducing starch and carbon nanomaterial titanium nitrile into the polymerization system and adjusting various process conditions, a heat-resistant, salt-resistant and pressure-resistant degradable water-absorbent resin is obtained, which improves the defects of ordinary polyacrylamide series water-absorbent resins, such as high water absorption rate, poor temperature and salt resistance, low gel strength after water absorption, non-degradability and non-compression resistance.

[0018] 2. The resin prepared by the present invention is a degradable and environmentally friendly resin, which can be used in oil field oil production, water injection and plugging, environmental sewage treatment, agriculture and forestry soil and water conservation, agricultural water storage and sanitary materials (such as diapers), etc. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the embodiments.

[0020] It should be noted that all raw materials used in the examples and comparative examples are commercially available unless otherwise specified, the acrylamide and 2-acrylamido-2-methylpropanesulfonic acid monomers used in the experiments are of polymerization grade, the conductivity of deionized water is ≤5 μs / cm, the crosslinking agent and initiator are all analytical grade reagents, and the nitrogen is high purity nitrogen.

[0021] Example 1 (1) Dispersion of carbon nanomaterials: Add 0.0003 g of nano-titanium nitrile and 70 g of deionized water into a beaker and place it in a 25,000 Hz ultrasonic cleaner for 30 minutes until no flocs are observed with the naked eye. (2) Starch gelatinization: Add 2 g of starch to the solution obtained in step (1), stir evenly, heat to 70° C., and gelatinize for 30 minutes to obtain a carbon nanomaterial starch solution; (3) Aqueous solution polymerization: 15 g acrylamide, 5 g 2-acrylamido-2-methylpropanesulfonic acid, 4.4 g sodium bicarbonate, 0.03 g N,N-methylenebisacrylamide and the carbon nanomaterial starch solution obtained in step (2) are added into a closed polymerization vessel, nitrogen is passed through the polymerization vessel to deoxygenate, so that the oxygen content of the system is less than 0.2 ppm, and the polymerization system temperature in the polymerization vessel is adjusted to 40° C. Then, 0.024 g ammonium persulfate and 0.024 g sodium bisulfite dissolved in 3.6 g deionized water are added into the polymerization vessel to carry out polymerization reaction. The viscosity of the system increases significantly. At this time, nitrogen is stopped and the polymerization is allowed to stand for 5 hours to obtain a polymerized colloid product with rubber elasticity. (4) Colloid post-treatment: The polymerized colloid product is cut into small pieces and fed into a granulator for granulation, dried at 70°C until the solid content reaches 96%, and then crushed and sieved to obtain 80-100 mesh as the final product, i.e., the biodegradable super absorbent resin.

[0022] Embodiment 2-3 Refer to Example 1, the only difference is that the polymerization reactor temperature at the beginning of the polymerization reaction is 10°C (Example 2) and 30°C (Example 3).

[0023] Embodiment 4-5 Refer to Example 1, the only difference is that the polymerization reaction time is 4 hours (Example 4) and 6 hours (Example 5).

[0024] Comparative Example 1 Referring to Example 1, the only difference is that no carbon nanomaterial is added, and 2 g of starch is directly added to 70 g of deionized water for gelatinization.

[0025] Comparative Example 2 Refer to Example 1, the only difference being that 2-acrylamido-2-methylpropanesulfonic acid was not added.

[0026] Comparative Example 3 Referring to Example 1, except that starch was not added, 0.0003 g of nano titanium nitrile and 72 g of deionized water were added into a beaker and ultrasonically dispersed.

[0027] Comparative Example 4 Refer to Example 1, the only difference is that nano-montmorillonite is used instead of nano-titanium nitrile.

[0028] Comparative Example 5 Refer to Example 1, the only difference is that carbon nanotubes are used instead of nano-titanium nitrile.

[0029] Comparative Example 6 Refer to Example 1, the only difference is that graphene is used instead of nano-titanium nitrile addition.

[0030] Comparative Example 7 Referring to Example 1, the only difference is that the nano-titanium nitrile is not dispersed by ultrasound, but directly added to the polymerization system. 0.0003 g of nano-titanium nitrile, 70 g of deionized water, and 2 g of starch are mixed, stirred evenly, and polymerized after gelatinization.

[0031] Comparative Example 8 The copolymerization of acrylamide and starch without adding titanium nitrile and AMPS is carried out as follows: (1) Starch gelatinization: Mix 2 g starch and 70 g deionized water, stir evenly, heat to 70 °C, and gelatinize for 30 minutes to obtain a starch solution; (2) Aqueous solution polymerization: 15 g acrylamide, 4.4 g sodium bicarbonate, 0.03 g N,N-methylenebisacrylamide and the starch solution obtained in step (2) were added into a closed polymerization vessel, nitrogen was passed through the polymerization vessel to deoxygenate, and the oxygen content of the system was less than 0.2 ppm. The polymerization system temperature in the polymerization vessel was adjusted to 40° C. Then, 0.024 g ammonium persulfate and 0.024 g sodium bisulfite dissolved in 3.6 g deionized water were added into the polymerization vessel to carry out polymerization reaction. The viscosity of the system increased significantly. At this time, the nitrogen was stopped and the polymerization was allowed to stand for 5 hours to obtain a polymerized colloidal product. (4) Colloid post-processing: The polymerized colloid product is cut into small pieces and fed into a granulator for granulation. It is dried at 70°C until the solid content reaches 96%, and then crushed and sieved to obtain 80-100 mesh as the final product.

[0032] Comparative Example 9 Refer to Example 1, the only difference is that the starch is not gelatinized by heating.

[0033] Comparative Example 10 Refer to Example 1, the only difference is that the polymerization reactor temperature is 70°C when the polymerization reaction starts.

[0034] The resins prepared in Examples 1 to 5 and Comparative Examples 1 to 10 were subjected to performance tests, and the test indicators included water absorption rate, water absorption rate after pressurization, and degradation residue. The results are shown in Table 1.

[0035] Table 1 Water absorption rate of resin in pure water and salt water and the residual amount after degradation under elevated temperature and pressure It can be seen from Table 1 that compared with the embodiments, in Comparative Example 1, titanium nitride is not added, and the compressive resistance of the water-absorbing resin decreases. In Comparative Example 2, AMPS is not added, and the heat and salt resistance is poor. In Comparative Example 3, when starch is not added, the resin absorbs water for 6 months and only degrades by 0.05. In Comparative Example 4, nano-montmorillonite is used to replace nano-titanium nitride, and the compressive resistance decreases the most. The compressive resistance of Comparative Examples 5 and 6 also decreases a lot. Comparative Examples 7 and 9 are respectively nano-titanium nitride is not ultrasonically dispersed and starch is not gelatinized. Nano-titanium nitride and starch are not evenly dispersed in the solution, and their compressive resistance and degradation performance are both reduced. The water-absorbing resin prepared by pure acrylamide in Comparative Example 8 has the lowest heat, salt and pressure resistance. It can be seen from Examples 1 to 3 and Comparative Example 10 that the initial temperature of the polymerization reaction, a lower polymerization temperature is beneficial to improving the water absorption rate.

Claims

1. A method for preparing a degradable super absorbent resin, characterized in that: The following steps are involved: (1) Dispersion of carbon nanomaterials: Mix the carbon nanomaterials and deionized water and disperse them by ultrasonic until there are no flocs; (2) Starch gelatinization: Add starch to the solution obtained in step (1), stir evenly, and heat to gelatinize to obtain a carbon nanomaterial starch solution; (3) Aqueous solution polymerization: acrylamide (AM), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), a hydrolyzing agent, a cross-linking agent and the carbon nanomaterial starch solution obtained in step (2) are added into a closed polymerization vessel. After the polymerization vessel is deoxygenated, an initiator dissolved in deionized water is added into the polymerization vessel to carry out a polymerization reaction to obtain a polymerized colloid product. (4) Colloid post-treatment: granulating, drying and crushing the polymerized colloid product to obtain the final product, i.e., the degradable super absorbent resin.

2. The method for preparing a degradable super absorbent resin according to claim 1, characterized in that: The carbon nanomaterial is titanium nitrile.

3. The method for preparing a degradable super absorbent resin according to claim 1, characterized in that: When the polymerization reaction starts, the polymerization reactor temperature is 10-40°C and the reaction time is 4-6 hours.

4. The method for preparing a degradable super absorbent resin according to any one of claims 1 to 3, characterized in that: The amounts of raw materials required in the preparation process are calculated by weight as follows: 0.0003 parts of carbon nanomaterials, 73.6 parts of deionized water, 2 parts of starch, 15 parts of acrylamide, 5 parts of 2-acrylamido-2-methylpropanesulfonic acid, 4.4 parts of hydrolyzing agent, 0.03 parts of crosslinking agent, and 0.048 parts of initiator.

5. The method for preparing a degradable super absorbent resin according to claim 4, characterized in that: The amount of deionized water used in step (1) is 70 parts, and the amount of deionized water used in step (3) is 3.6 parts.

6. The method for preparing a degradable super absorbent resin according to claim 4, characterized in that: The hydrolyzing agent is sodium hydroxide, sodium carbonate or sodium bicarbonate.

7. The method for preparing a degradable super absorbent resin according to claim 4, characterized in that: The crosslinking agent is N,N-methylenebisacrylamide.

8. The method for preparing a degradable super absorbent resin according to claim 4, characterized in that: The initiator is a combination of an oxidizing agent and a reducing agent in a mass ratio of 1:

1.

9. The method for preparing a degradable super absorbent resin according to claim 8, characterized in that: The oxidizing agent is one or more of ammonium persulfate, potassium persulfate or sodium persulfate.

10. The method for preparing a degradable super absorbent resin according to claim 8, characterized in that: The reducing agent is one or both of sodium bisulfite and sodium sulfite.

Citation Information

Patent Citations

  • Preparation method of salt-resistant water-absorbent resin with high water absorption rate

    CN103709309A

  • Preparation method of salt-tolerant super absorbent polymer (SAP)

    CN104140491A

  • Anti-static / conductive polyimide resin as well as preparation method and application thereof

    CN109880094A

  • Super absorbent resin containing montmorillonite and preparation method thereof

    CN109970917A

  • Production method of water-absorbent resin, water-absorbent resin, and usage of water-absorbent resin

    JP2007077393A